A Systematic Review of Serious Games in Training Health Care Professionals. Issue 1 (February 2016) - Wang, Ryan; DeMaria, Samuel; Goldberg, Andrew; Katz, Daniel
Abstract : Summary Statement: Serious games are computer-based games designed for training purposes. They are poised to expand their role in medical education. This systematic review, conducted in accordance with PRISMA guidelines, aimed to synthesize current serious gaming trends in health care training, especially those pertaining to developmental methodologies and game evaluation. PubMed, EMBASE, and Cochrane databases were queried for relevant documents published through December 2014. Of the 3737 publications identified, 48 of them, covering 42 serious games, were included. From 2007 to 2014, they demonstrate a growth from 2 games and 2 genres to 42 games and 8 genres. Overall, study design was heterogeneous and methodological quality by MERQSI score averaged 10.5/18, which is modest. Seventy-nine percent of serious games were evaluated for training outcomes. As the number of serious games for health care training continues to grow, having schemas that organize how educators approach their development and evaluation is essential for their success. Abstract : Supplemental digital content is available in the text.